Rancang Bangun Sistem Informasi Penjualan Toko Eight Point Store Berbasis Website - Kristianti, Novera; Rahman, Resha Ananda (Journal of Information Technology and Computer Science, 2022)
E-commerce can be interpreted as a way of using internet facilities for online shopping or trade or direct sales, where a website can provide "get and deliver" services. E-commerce is a very effective way of marketing products or services at this time, which requires business actors to provide convenience to consumers. The convenience that can be enjoyed by consumers, such as buyers can use mobile devices to view products, access merchandise, store information, order, and pay while traveling or anywhere. Not only that, the existence of a website will be able to expand the reach of marketing, so a web-based application is needed to support the process of marketing and order products. By having your e-commerce website, shops can build their business brand, then they can increase the credibility of the business and look more bona fide, consumers can easily get the latest information, can always be accessed, have a wider target market, provide a place to show products, customers will focus on the product offered. In this research, in designing and building an application using the Waterfall model SDLC method. In the Waterfall stage it flows by completing one stage and then moving to the next stage such as a Waterfall, this stage sequentially starts from the analysis, design, implementation, testing, distribution, and support stages. This website has features for purchasing products by paying via bank transfer, and the admin section can manage product data and print sales reports in a day, month, and year format. Using the Black box results from research on the Eight point store Shop Sales Information System Website can perform functions according to its purpose.